Analisis Sistem Akuntansi Pemberian Kredit Pemilikan Rumah (KPR) pada PT Bank Central Asia Tbk Cabang Pettarani Makassar - Gafur, Abd; Syah, Sri Rahayu; Julkifli, Julkifli; Irmawati, Ika (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study aims to understand the home ownership credit accounting system at PT Bank Central Asia Tbk Pettarani Makassar Branch, with a focus on simple requirements and a fast credit application process. Based on research conducted at PT Bank Central Asia Tbk Pettarani Makassar Branch, the use of the MyCore application in providing home ownership credit can facilitate the input of prospective debtor files in an effective and efficient manner, thereby speeding up the process. The author applies a qualitative research method, which produces descriptive data in the form of written notes and oral information from individuals observed during data collection in the field. The results of the study show that the process of applying for a home ownership loan at PT Bank Central Asia Tbk Pettarani Makassar Branch has become easier and faster because the requirements applied are general requirements that are already owned by customers. This allows the collection of files to be done more quickly.